Analisis Kinerja Keuangan Berdasarkan Financial Value Added (FVA) dan Kaitannya dengan Manfaat Ekonomi pada Koperasi Dharma Nirmala Mandiri Kota Bandung - Endang Wahyuningsih; Wahyudin Wahyudin (LPPM Universitas Koperasi Indonesia, 2025)
This study aims to analyze financial performance using the Financial Value Added (FVA) method and its relation to the economic benefits generated for members. The research focuses on assessing whether the implementation of FVA as a performance measurement tool effectively reflects the financial value created and distributed to members. A quantitative approach was employed, using financial statement data as the primary source of analysis. The findings indicate that FVA serves as a reliable metric to evaluate financial performance, particularly in organizations with a member-oriented structure. Furthermore, the study highlights the significant correlation between positive FVA outcomes and the economic benefits accrued by members. These results provide valuable insights for decision-makers to enhance financial strategies and ensure sustainable member benefits.